Strengthening Youth Capacity in Nagari Situmbuk through Interactive English Teaching, Digital Marketing, and Cinematography for Creative Village Promotion - Witri Oktavia; Dinovia Fannil Kher; Yuli Tiarina; Ratmanida; An Fauzia Rozani Syarif (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2026)
This community service program was conducted in Nagari Situmbuk, Tanah Datar Regency, an area with strong potential in community-based education, village tourism, and UMKM development. However, these potentials had not been fully realized due to limited youth capacity to conduct interactive English learning activities and the continued conventional use of digital media for tourism and UMKM promotion. This program aimed to strengthen youth capacity through integrated training in interactive English teaching, digital marketing, and basic cinematography to promote creative villages. The program employed a participatory approach involving the COIV youth community, UMKM actors, and village stakeholders. Its implementation consisted of four main stages: needs analysis, training workshops, field mentoring, and participatory evaluation. The program involved 20 participants, consisting of youths and UMKM actors. The results show that participants improved their capacity to conduct communicative and contextual English-learning activities, gained practical understanding of social-media-based promotion for local products, and produced simple promotional videos highlighting the cultural and natural potential of Nagari Situmbuk. The program also encouraged the emergence of local youth cadres capable of sustaining English-learning initiatives and supporting village promotion efforts. These findings suggest that integrating pedagogical, digital, and creative media training can serve as a practical model for strengthening youth-led village empowerment.